Late repression of NF-κB activity by invasive but not non-invasive meningococcal isolates is required to display apoptosis of epithelial cells. - Ala-Eddine Deghmane; Hela El Kafsi; Dario Giorgini; Aziza Abaza; Muhamed-Kheir Taha (PLoS Pathogens, 2011)
Meningococcal invasive isolates of the ST-11 clonal complex are most frequently associated with disease and rarely found in carriers. Unlike carriage isolates, invasive isolates induce apoptosis in epithelial cells through the TNF-α signaling pathway. While invasive and non-invasive isolates are both able to trigger the TLR4/MyD88 pathway in lipooligosaccharide (LOS)-dependant manner, we show that only non-invasive isolates were able to induce sustained NF-κB activity in infected epithelial cells. ST-11 invasive isolates initially triggered a strong NF-κB activity in infected epithelial cells that was abolished after 9 h of infection and was associated with sustained activation of JNK, increased levels of membrane TNFR1, and induction of apoptosis. In contrast, infection with carriage isolates lead to prolonged activation of NF-κB that was associated with a transient activation of JNK increased TACE/ADAM17-mediated shedding of TNFR1 and protection against apoptosis. Our data provide insights to understand the meningococcal duality between invasiveness and asymptomatic carriage.